Penentuan Lingkungan Batimetri Berdasarkan Fosil Foraminifera Daerah Wonoharjo dan Sekitarnya,Kabupaten Kebumen-Banyumas,Jawa Tengah - Suci Adelia Rahmawati; Edy Sutriyono (Fakultas Teknik Universitas Sriwijaya, 2023)
This research was conducted in Wonoharjo located Kebumen-Banyumas Regency. This area belongs to the Halang Formation with sandstone rock units that belong to the South Serayu Basin. The research method used in this study is descriptive paleontology analysis with the sampling of sandstone taken from two different rivers which are Wonoharjo river and Lemungsur river, followed by laboratory analysis. This research aims to find out paleobatimetry. Based on laboratory analysts' results, there is obtained bentonic foraminifera from several species namely, Pyrgo depressa, Clavulina pacifica, Monalysidium politum, Nodosaria calenulata, Operculina ammonoides, Slioostoniella fisluca, Streblus becarri, Clavulina pacifica, Technitella legume, Amphicoryna scalaris. With the discovery of bentonic foraminifera fossils can be interpreted that the Halang Formation sandstone unit found in the Wonoharjo river has a batimetry environment, which is the edge Neritik zone with a relative age range of the Middle Miocene. While the sandstone Halang Formation found in the Wonoharjo river has a batimetry environment, namely the Middle Neritic zone to outer Neritic with a relative age range of the Middle Miocene.